Methylglyoxal: A Key Factor for Diabetic Retinopathy and Its Effects on Retinal Damage - Vladlen Klochkov; Chi-Ming Chan; Wan-Wan Lin (Biomedicines)
Background: Diabetic retinopathy is the most common retinal vascular disease, affecting the retina’s blood vessels and causing chronic inflammation, oxidative stress, and, ultimately, vision loss. Diabetes-induced elevated glucose levels increase glycolysis, the main methylglyoxal (MGO) formation pathway. MGO is a highly reactive dicarbonyl and the most rapid glycation compound to form endogenous advanced glycation end products (AGEs). MGO can act both intra- and extracellularly by glycating molecules and activating the receptor for AGEs (RAGE) pathway. Conclusions: This review summarizes the sources of MGO formation and its actions on various cell pathways in retinal cells such as oxidative stress, glycation, autophagy, ER stress, and mitochondrial dysfunction. Finally, the detoxification of MGO by glyoxalases is discussed.